Effects of resistant starch consumption on anthropometric and serum parameters in adults with metabolic syndrome-related risks: a systematic review and meta-analysis - Lin, Ximing; Li, Zaizhen; Zheng, Dongyuan; Du, Ruofang; Zhong, Ruikang; Lin, Changqing; Meng, Hua (Frontiers in Nutrition, 2025)
BackgroundThe effects of resistant starch (RS) consumption on anthropometric and serum biomarkers in adults with metabolic syndrome (MetS)-related risks, each component of which similarly increases the incidence of cardiovascular disease, have yielded inconclusive results when compared to anticipated outcomes. The heterogenous effects of RS type, delivery mode, participant characteristics, intervention conditions, and the quality of study design on the observed outcomes are considered to be insufficiently understood.MethodsA comprehensive search was conducted in five public databases and 30 previously published meta-analyses up to January 21, 2025, following the PRISMA guidelines. A total of 23 parallel or crossover randomized controlled trials were included for qualitative analysis via Cochrane Risk of Bias tool and the Jadad scale. Among, 19 studies were included for synthesizing effect sizes of changes in anthropometric parameters, glycemic and lipid profiles, inflammatory markers, and oxidative stress biomarkers using a random-effects model. Subgroup analysis was performed to explore contributes of heterogeneity. Sensitivity analysis and publication bias analysis were conducted.ResultsRS consumption was associated with significant reductions in hip circumference (MD = −1.83 cm; 95% CI: −2.03 to −1.64), total cholesterol (MD = −0.20 mmol/L; 95% CI: −0.32 to −0.08), low-density lipoprotein cholesterol (MD = −0.11 mmol/L; 95% CI: −0.18 to −0.04), and improved superoxide dismutase levels (SMD = 0.29; 95% CI: 0.08–0.51). Waist circumference, fasting insulin, HOMA-IR, and TNF-α were reduced by RS with high heterogeneity yet. High quality of study design, participants with younger age and overweight, a supplement as delivery, a dose of up to 30 g/day, and lasting over 8 weeks partly influenced the effects.ConclusionSteady effects of RS were observed on hip circumference, total cholesterol, low-density lipoprotein cholesterol, and superoxide dismutase in adults with MetS-related risks. For the intervention with RS, it is recommended that participants be younger and overweight, with a dosage of at least 30 g/day, and over a period of 8 weeks. Future studies should be designed with high methodological quality, with considerations of delivery mode, properties, as well as gut microbiome and metabolome.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251014654 CRD420251014654.